Researching Factors that Affect the Shopping Decisions of Shopping in Tiktok - Nguyen, Thi Van Trang; Nguyen, Thi Thu Thuy; Do, Thi Thanh Tam (INTI International University, 2024)
In recent years, Tiktok Shop, a social networking platform that was born, has been changing the landscape of the e-commerce market. The way of shopping through short videos is a new method of shopping and the key to the success of TikTok. When customers watch short videos, TikTok will build on consumer habits and journeys to better meet user needs. The article analyzed the influence of 9 factors on the purchase intention of users based on the combination of the Theory of Reasoned Action (TRA) and the Technology Acceptance Model (TAM). The result shows that there are 4 factors that directly and positively affect shopping behavior: "Opinion of the reference group", "My own beliefs", "Videomaker", and "Perceived value". Thus, the article proposes appropriate and practical solutions to help sellers better understand customer psychology and have strategies to keep the consumers and increase sales efficiency.